Impact of Globalization on Macroeconomic Statistics - -, Fahad Fayaz (2024)
This thesis critically assesses whether traditional economic measures such as GDP are still relevant to their users in today’s fast-evolving economic environment. It explicitly aims to understand it within the context of globalization’s significant impact on macroeconomic indicators. In other words, we need to know whether macroeconomic indicators are relevant globally; if not, what should we do as statisticians to stay relevant? Furthermore, this study addresses how updates to the System of National Accounts (SNA) affect the operations and output produced by statistical offices. An innovative aspect of this thesis is also to propose methodological improvements in existing macroeconomic measurements to better reflect the realities of today’s interconnected world. Lastly, the thesis uses cluster analysis to evaluate the effects of globalization on different countries. Specifically, it identifies which OECD countries are substantially affected by globalization and which are less affected. Similarly, it examines non-OECD countries to determine those substantially impacted by globalization and those less affected by globalization.